Quantitative proteomics unravels that the post-transcriptional regulator Crc modulates the generation of vesicles and secreted virulence determinants of Pseudomonas aeruginosa - Jose Antonio Reales-Calderón; Fernando Corona; Lucía Monteoliva; Concha Gil; Jose Luis Martínez (Data in Brief, 2015)
Crc is a post-transcriptional regulator in Pseudomonas aeruginosa that modulates its metabolism, but also its susceptibility to antibiotics and virulence. Most of P. aeruginosa virulence factors are secreted or engulfed in vesicles. A Crc deficient mutant was created and the extracellular vesicles associated exoproteome and the vesicle-free secretome was quantified using iTRAQ. Fifty vesicles-associated proteins were more abundant and 14 less abundant in the Crc-defective strain, whereas 37 were more abundant and 17 less abundant in the vesicle-free secretome. Different virulence determinants, such as ToxA, protease IV, azurin, chitin-binding protein, PlcB and Hcp1, were less abundant in the Crc-defective mutant. We also observed that the crc mutant presented an impaired vesicle-associated secretion of quorum sensing signal molecules and less cytotoxicity than its wild-type strain, in agreement with the low secretion of proteins related to virulence. Our results offer new insights into the mechanisms by which Crc regulates P. aeruginosa virulence, through the modulation of vesicle formation and secretion of both virulence determinants and quorum sensing signals.